PHASE BEHAVIOR STUDIES OF ALPHA OLEFIN SULFONATE (AOS), LAURYL GLUCOSIDE, AND DECANE IN CREATING WINSOR TYPE-III MICROEMULSION - MOHD SHAH, MUHAMMAD FIRDAUS (2021)
Chemical enhanced oil recovery (cEOR), specifically, surfactant flooding is carried out by injecting surfactants into the reservoir to improve the ultimate recovery of the field.